Comets And The Origin Of Life. (World Scientific, 2009)
The idea that comets may be connected with the origin of life on Earth was considered heresy a few decades ago, with scientists shying away from this possibility as if from a medieval superstition. However the case that comets may have contributed at least the complex organic building blocks of life has become very strong, and mechanisms have now been identified whereby comets may incubate and transfer microbial life from one cosmic habitat to another in the Galaxy. The latter process cometary panspermia was pioneered by the late Sir Fred Hoyle and one of the present authors in the early 1980'